'It doesn't bother me...I'm here for a reason': a qualitative examination of white college athletes' experiences at a historically black college/university (HBCU). Issue 1 (2nd January 2021) - Newton, Ajhanai Channel Inez; Cooper, Joseph N.
ABSTRACT: The purpose of this study was to explore the academic, athletic, and social experiences of White college athletes at a Division I historically Black college/university (HBCU). Previous research has documented how White college athletes experience positive educational and developmental outcomes at historically White institutions (HWIs). However, there is a dearth of research on White college athletes' experiences where they are the demographic minority within collegiate institutions like HBCUs. Three focus groups and four individual interviews were conducted and the data from four White college athletes at a HBCU were examined for the current study. Using symbolic interactionism and interpretive interactionism as theoretical lenses, key findings revealed participants largely expressed satisfaction with their academic, athletic, and social experiences. Implications for policy and practice are discussed.